ENZYMATIC ACTIVITY OF CELLULASE BASIDIOMYCETES PREPARATIONS AND LOWER FUNGI - К. Г. Древаль; М. І. Бойко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2012)
There were conducted the comparative analysis of cellulases enzymatic preparations of basidiomycetes with lower fungi both commercial and laboratory origin. In the process of comparing the preparations were investigated as to their activity to hydrolyze filter paper, Nacarboxymethylcellulose and cellobiose. pH and temperature optima of preparations action, dependence of their activity upon holding time at optimal pH and temperature were determined. It is proved that cellulolytic enzymes from basidiomycetes are more active than those from lower fungi. It is found that cellulases from both basidiomycetes and lower fungi exhibit a number of associated enzymatic activities, but cellulolytic enzymes from basidiomycetes have significantly higher activity of enzymes that as to starch, pectin and lignin